(untitled) (Journal of the College of Basic Education, 2023)
Overtaking settlements in some cities, especially in developing countries, constitute a phenomenonclear and included in the structure of the housing system therein. There is no doubt that housing is a basic needAfter food and clothing, a person strives in his life to obtain housing.secures the life of his family. Housing represents a place for shelter and a vessel for social upbringing, and in it he spends his life.The individual spends about 68-75% of his total time (1). It also highlights the importance of residential use, includingOccupying space in the structure of human settlements. The percentage of this use in the city of BaghdadAbout 62.6% of the total area of land covered by development and estimated at that timeB 238.4, km 2 in the year (2) 1975. In New Delhi, this percentage was 41.9% inIn 1956, New York City accounted for 23.2% of the built-up area (3). This is due to the severity of the intensityVertical housing development and rapid transit systems therein.